Implementasi Sensor LDR Pada Prototipe Sistem Tracking Dual Axis Untuk Deteksi Arah Sinar Matahari Pada Sel Surya - Dekki Widiatmoko; Rachmat Setiawibawa; Rafi Maulana Al-farizi; Mokhammad Syafaat; Eriski Prawira (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Solar energy is a potential solution to meet the electricity needs of TNI AD posts and bases in border areas. However, conventional solar energy systems have limited efficiency because they can only absorb sunlight from one direction. The efficiency of solar energy systems can be improved by using a dual-axis tracking system equipped with a LDR sensor. The LDR sensor is used to detect the direction of sunlight. The change in the LDR sensor resistance due to the change in the intensity of light that hits it is then processed by a microcontroller to move the solar panel in the appropriate direction. Based on the results of testing, the dual-axis tracking system with an LDR sensor significantly increases the power generated compared to conventional solar energy systems. At the peak of performance during dynamic testing at 12:00 pm, the total power reached 2,196 W, while the static test reached a total power of 1,311 W. Therefore, the dual-axis tracking system with an LDR sensor can be a more optimal choice to improve the performance and efficiency of solar energy systems in generating electricity at TNI AD posts and bases in border areas.